Analisis Faktor yang Memengaruhi Perkembangan Anak - Aida Fitria; Helda Iu (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
In 2018, the World Health Organization (WHO) reported prevalence data of 28.7% for children under 5 years of age with failure to thrive and developmental disabilities. According to data from the Seisemayan Health Center, two children have speech problems and one has autism. During infancy, there are many changes in growth and development. That is, fast range and slow range. The purpose of the study was to analyze the factors that influence the growth and development of children in the working area of the Seisemayan Health Center. This type of survey is a cross-sectional approach to analytical research. The population consists of all mothers who have children over the age of 56 years as many as 228 people, and using stratified random sampling so that a sample of 69 respondents is obtained. Data analysis used univariate and bivariate analysis using chi-square test. The result of this research is p-value = 0.002. Respondents had a history of infection with a p-value of 0.267. When raising a child with a p value = 0.003. The conclusion shows that there is an influence of mother's knowledge and parenting, as well as infection history factors and birth weight have no effect on child growth and development in the work area of the Seisemayan Health Center. Health care professionals are encouraged to improve communication, information and education regarding parental child development.